Generation and characterization of an antagonistic monoclonal antibody against an extracellular domain of mouse DP2 (CRTH2/GPR44) receptors for prostaglandin D(2) - Nagata, Nanae (PLoS One, 2017)
Prostaglandin D(2) (PGD(2)) is a lipid mediator involved in sleep regulation and inflammation. PGD(2) interacts with 2 types of G protein-coupled receptors, DP1 and DP2/CRTH2 (chemoattractant receptor homologous molecule expressed on T helper type 2 cells)/GPR44 to show a variety of biological effects. DP1 activation leads to Gs-mediated elevation of the intracellular cAMP level, whereas activation of DP2 decreases this level via the Gi pathway; and it also induces G protein-independent, arrestin-mediated cellular responses. Activation of DP2 by PGD(2) causes the progression of inflammation via the recruitment of lymphocytes by enhancing the production of Th2-cytokines. Here we developed monoclonal antibodies (MAbs) against the extracellular domain of mouse DP2 by immunization of DP2-null mutant mice with DP2-overexpressing BAF3, murine interleukin-3 dependent pro-B cells, to reduce the generation of antibodies against the host cells by immunization of mice. Moreover, we immunized DP2-KO mice to prevent immunological tolerance to mDP2 protein. After cell ELISA, immunocytochemical, and Western blot analyses, we successfully obtained a novel monoclonal antibody, MAb-1D8, that specifically recognized native mouse DP2, but neither human DP2 nor denatured mouse DP2, by binding to a particular 3D receptor conformation formed by the N-terminus and extracellular loop 1, 2, and 3 of DP2. This antibody inhibited the binding of 0.5 nM [(3)H]PGD(2) to mouse DP2 (IC(50) = 46.3 ± 18.6 nM), showed antagonistic activity toward 15(R)-15-methyl PGD(2)-induced inhibition of 300 nM forskolin-activated cAMP production (IC(50) = 16.9 ± 2.6 nM), and gave positive results for immunohistochemical staining of DP2-expressing CD4+ Th2 lymphocytes that had accumulated in the kidney of unilateral ureteral obstruction model mice. This monoclonal antibody will be very useful for in vitro and in vivo studies on DP2-mediated diseases.